Human Capital Strategy In Improving The Quality Of Human Resources : A Systematic Literature Review - Murdiono, Jatmiko; Hamidah, Hamidah; Sudiarditha, I Ketut R (International Journal of Advanced Multidisciplinary, 2024)
Humans are an important asset in any organization or company. As a valuable resource, humans are assets that need to be managed properly. Therefore, a human capital strategy is needed to improve the quality of human resources. This study uses a systematic literature review approach to analyze human capital strategies for improving the quality of human resources. The data collected through Google Scholar and Mendeley.com was analyzed, summarized, described, and concluded. This research has contributed to providing guidance for organizations or companies to develop a human model strategy. The limitation of this research is that it only uses limited references collected from the search engine used so that researchers in the future can research more deeply about human capital strategies for a certain sector or several sectors.